Childhood sleeping difficulties and depression in adulthood: the 1970 British Cohort Study. (2nd September 2014) - Greene, Giles; Gregory, Alice M.; Fone, David; White, James
Summary Sleeping difficulties in childhood have been associated with an increased risk of depression in adult life, but existing studies have not accounted for comorbid maternal sleeping difficulties and depression. This study aimed to determine the association between childhood sleeping difficulties and depression in adulthood after adjusting for the potential confounding influences of maternal depression and sleeping difficulties. Data from the British Cohort Study 1970, a prospective birth cohort with 30 years of follow‐up (1975–2005) were used. At 5 years of age, 7437 parents of participants recorded information on whether their child had sleeping difficulties, the frequency of bed‐wetting, nightmares, maternal depression and sleep difficulties. At 34 years of age, participants reported whether or not they had received medical treatment for depression in the past year. Parental reports of severe sleeping difficulties at 5 years were associated with an increased risk of depression at age 34 years [odds ratio (OR) = 1.9, 95% confidence interval (CI) = 1.2, 3.2] whereas moderate sleeping difficulties were not (OR = 1.1, 95% CI = 0.9, 1.3). In conclusion, severe sleeping problems in childhood may be associated with increased susceptibility to depression in adult life.